Glucocorticoid induced adrenal insufficiency. (12th July 2021) - Prete, Alessandro; Bancos, Irina
ABSTRACT: Synthetic glucocorticoids are widely used for their anti-inflammatory and immunosuppressive actions. A possible unwanted effect of glucocorticoid treatment is suppression of the hypothalamic-pituitary-adrenal axis, which can lead to adrenal insufficiency. Factors affecting the risk of glucocorticoid induced adrenal insufficiency (GI-AI) include the duration of glucocorticoid therapy, mode of administration, glucocorticoid dose and potency, concomitant drugs that interfere with glucocorticoid metabolism, and individual susceptibility. Patients with exogenous glucocorticoid use may develop features of Cushing's syndrome and, subsequently, glucocorticoid withdrawal syndrome when the treatment is tapered down. Symptoms of glucocorticoid withdrawal can overlap with those of the underlying disorder, as well as of GI-AI. A careful approach to the glucocorticoid taper and appropriate patient counseling are needed to assure a successful taper. Glucocorticoid therapy should not be completely stopped until recovery of adrenal function is achieved. In this review, we discuss the factors affecting the risk of GI-AI, propose a regimen for the glucocorticoid taper, and make suggestions for assessment of adrenal function recovery. We also describe current gaps in the management of patients with GI-AI and make suggestions for an approach to the glucocorticoid withdrawal syndrome, chronic management of glucocorticoid therapy, and education on GI-AI for patients and providers.